Comparison of the Effects of Strontium Ranelate and Raloxiphene on Bone Mineral Density in Postmenopausal Osteoporosis - Original Investigation - Figen Yılmaz; Beril Doğu; Tülay Şahin; Füsun Şahin; Banu Kuran (Galenos Yayinevi, 2009)
Aim: To compare the effects of one year- long strontium ranelate (SR) and raloxiphene ( R) therapies on bone mineral densities (BMDs) in postmenopausal osteoporotic women. Material and Methods: Female patients diagnosed as postmenopausal osteoporosis who received SR 2 gr/d (Group 1) or R 60 mg/d (Group 2) were analysed retrospectively.. All the patients also received calcium 1000 mg/d, vitamin D 880 IU/d supplementations. Patients also underwent BMD measurements from L2-4, femoral neck and femur total with Lunar-DXA before and after the treatment. Intragroup changes in yearly BMD and t values were calculated and compared with each other. Results: Both groups contained 22 patients without any significant inter-group differences between age, menarche age, duration of postmenopausal period, weight, height, body mass indexes, baseline BMDs and t values (p>0.05). After a year-long treatment, a significant improvement in BMD of L2-4 in Group 1 was detected (p<0.0001). In posttreatment t values of the same group a significant improvement was seen for all three regions examined (p<0.05). In Group 1, none of these regions showed significant improvements as for BMD and t values. Conclusion: After a year-long treatment, strontium ranelate demonstrated significant improvements as for BMDs of L2-4, and t values in L2-4, femoral neck, and femur total. An increase in BMDs of femoral neck and femur total was seen which didn't attain significance. However raloxiphene didn't lead to significant improvement in BMDs and t values of the three regions examined. After a year-long treatment strontium ranelate was found to be more effective than raloxiphene in terms of improvements in BMDs. (From the World of Osteoporosis 2009;15:16-20)